Descriptive Study Of Teachers’ Loyalty In Yaa Bunayya 1 Kindergarten, Surabaya - Tika Izzatul (Airlangga Development Journal, 2022)
Teachers’ loyalty is an important thing as frequent teachers’ turnover will have negative effect towards students. Teachers in Yaa Bunayya 1 Kindergarten Surabaya are highly loyal towards their school, where most teachers had worked for more than 3 years even though their wages are below minimum payment in Surabaya City. This study aimed to magnify factors that contribute towards teacher’s loyalty upon their organization aside from financial reward. This study used semi-structural interview with teachers that has worked in the school for at least 6 years, along with observation to obtain secondary data. Some things that contribute towards teachers’ loyalty aside from wage are work environment, relationship with co-workers and supervisors, and religious believe.